Reduction in asthma admissions during the COVID-19 pandemic: consequence of public health measures in Singapore. Issue 4 (8th April 2021) - Wee, Liang En; Conceicao, Edwin Philip; Tan, Jing Yuan; Sim, Jean Xiang Ying; Venkatachalam, Indumathi
We read with interest the study by Izquierdo et al . [1] that reported a lower proportion of patients with concurrent asthma and coronavirus disease 2019 (COVID-19), compared to other chronic diseases. During the ongoing pandemic, various studies have also observed a lower occurrence of persons with asthma amongst hospitalised COVID-19 cases [2, 3]. Several hypotheses have been postulated to account for these observations, including lower susceptibility to COVID-19 amongst patients with asthma [2, 3] and a remission in rates of common circulating respiratory viral infections (RVIs) [4]. RVIs are potential triggers of asthma exacerbations and may cause a loss of asthma control [5]. During the COVID-19 pandemic, community-wide public health measures introduced to reduce transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), such as universal masking and social distancing, may reduce community transmission of common RVIs [4], potentially decreasing the frequency and severity of asthma exacerbations and hence reducing hospitalisations. However, patients may demonstrate a higher threshold to seek care due to fear of nosocomial transmission during the pandemic. Significant community transmission of SARS-CoV-2 may thus confound causal interpretation of trends in asthma hospitalisations. While the ongoing pandemic provides a rare opportunity to ascertain the impact of public health measures on hospitalisations for asthma exacerbations, such observations are only possible in areas that have mitigated community transmission and maintained public health interventions over a sustained duration. A sustained reduction in asthma admissions with PCR-proven respiratory viral infections coincided with the widespread adoption of public health measures, including social distancing and wearing of face coverings, during a pandemic https://bit.ly/2Kug9iw